ISOLATION AND PHENOTYPIC CHARACTERIZATION OF MODERATE HALOPHILIC BACTERIA FROM ATHALOSALINE LAKE, DUMAT AL-JANDAL, IN EXTREME NORTH OF AL JOUF (KSA) - M. M. Al Enazi; Bilal Ahmad Tantry; Shaik Rahiman; A. Z. El-Bahrawy (European Scientific Journal, ESJ, 2014)
Introduction: Hypersaline intra-continental (athalassohaline) salt lakes represent an extreme type of habitat where halophilic prokaryotes are a dominant form of life. Bacteria are commonly found in natural environments containing significant concentration of NaCl. Dumat Al Jandal artificial Lake is a man-made water body located in Dumat Al Jandal, Al-Jouf province. This lake features numerous ecosystems including hypersaline environments in which microbial diversity has never yet been studied. Objective: We evaluate the presence of moderately halophilic microbial population in the lake extreme environments based on Physiochemical and Microbiological characterization. Methodology: Water samples were collected from the lake from different sites. Sample salinity was determined using a conductivity meter. Samples were diluted and cultured on a chemically defined medium (CDM) to grow halophilic bacteria. The density of halophiles was estimated by viable plate counts. A collection of isolates was selected, gram-stained, tested for catalase, and characterized using standard microbiological methods. Result: Growth occurred at 3-15%(W/V), NaCl (optimum 8%), pH 5– 9(optimum 7.5) and temperature 35-40oC(optimum 38oC). The density of halophilic bacteria in water samples ranged from 2.2×102 - 42×102 colony forming units per ml (cfu ml-1). Phenotypic results revealed members of the domain Bacteria only and the predominant genus were Halomonas and Bacillus followed by others. The majority of bacteria isolated were gramnegative, catalase-positive, and rods. Conclusion: Our trials paved an effective avenue of isolating moderate halophilic bacteria from this lake in order to promote saline-alkali soil-based agriculture, and it also serves as a source for halostable enzymes which offers potential applications in various pharmacochemical industries.